Forecasting Indonesia's ginger export with major competing countries in the international market - Elpawati, Elpawati; Wirhanti, Puspi Eko; Aisyah, Salma Nur (Anjoro: International Journal of Agriculture and Business, 2022)
The volatile and unbalanced global demand for ginger makes it difficult for Indonesia to realize the decline and rise in exports. An analysis of export relations among between China, India, the Netherlands, and Indonesia is indispensable as these countries are the main exporters of ginger worldwide. Therefore, this ginger-exporting study aims to analyze the relationship between ginger exporting countries Indonesia, China, India, and the Netherlands from January 2013 to December 2017. Investigate the shock effect of increasing Chinese, Indian, and the Netherlands ginger exports on Indonesian ginger exports from January 2018 to December 2024. Explore the effect of changes in ginger exports in the four countries from 2018 to 2024. Analysis of relationships and influences over the next 6 years from 2018-2024 was performed using a time-series timeseries in the form of ginger export data from Indonesia, China, India, and the Netherlands for the 2013-2017. The analysis method used VAR (VECM), while the data were processed using Microsoft Excel 2010 and EViews 10 applications. The results showed a relationship between the four4 countries in the long term, significantly affecting the increase and decrease ginger exports in Indonesia, the Netherlands, and India. Between the 2018-2024, Indonesia's ginger exports will increase by 92%, followed by the Netherlands 7%, China 0.2%, and India 0.8%. For the China, ginger exports will increase 80% followed by Indonesia 4%, India 5%, and the Netherlands 11%. Meanwhile, for Indian ginger, an increase in exports will be dominated by India at 68%, Indonesia 20%, China 6%, and the Netherlands 6%. As for the Netherlands ginger exports, there will be an increase dominated by Indonesia at 73%, China 1%, India 5%, and the Netherlands 21%.